2015
DOI: 10.2319/091014-637.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable attachment shapes and aligner material on aligner retention

Abstract: Objective: To evaluate the retention of four types of aligners on a dental arch with various attachments. Materials and Methods: For this study, three casts were manufactured, two of which contained attachments (ellipsoid and beveled), and one without any attachments to serve as a control. Four types of aligners were thermoformed: Clear-Aligner (CA)-soft, CA-medium, and CA-hard, with various thicknesses, and Essix ACE. Measurements of vertical displacement force during aligner removal were performed with the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 2 publications
4
50
0
1
Order By: Relevance
“…When evaluating the outcomes of clear aligner treatment, it should be considered that several factors play a role in determining successful tooth movement: the attachment’s shape and position [ 12 ], the aligner’s material and thickness [ 14 , 30 ], the amount of activation present in each aligner [ 31 ], and the techniques used for the production of the aligners [ 15 ]. To be thorough, treatment outcomes depend also on the patient’s characteristics, bone density and morphology [ 32 ], and crown and root morphology of the teeth [ 33 ], as well as on factors related to the clinician, like the accuracy in performing the requested amount of IPR, which is usually underestimated [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating the outcomes of clear aligner treatment, it should be considered that several factors play a role in determining successful tooth movement: the attachment’s shape and position [ 12 ], the aligner’s material and thickness [ 14 , 30 ], the amount of activation present in each aligner [ 31 ], and the techniques used for the production of the aligners [ 15 ]. To be thorough, treatment outcomes depend also on the patient’s characteristics, bone density and morphology [ 32 ], and crown and root morphology of the teeth [ 33 ], as well as on factors related to the clinician, like the accuracy in performing the requested amount of IPR, which is usually underestimated [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While levelling and aligning, intrusion, and bodily distalisation of upper molars of no more than 1.5 mm were demonstrated to be predictable movements, rotations, extrusion, and torque movements are difficult to achieve with clear aligners [ 8 11 ]. In addition, most of the available studies are relative to the Invisalign system, but differences in the aligner’s material properties and thickness, the production process, the model’s precision, and the position of the aligner’s margin all have an effect on the final performance of the appliance [ 12 15 ]; therefore, different results can be expected from different clear aligner systems [ 16 ]. Recently, Lombardo et al [ 16 ], comparing planned and achieved tipping and rotation tooth movements in patients using another clear aligners system, found that orthodontic aligners are unable to achieve programmed movement with 100% predictability.…”
Section: Introductionmentioning
confidence: 99%
“…Several related features help the achievement of successful clear aligner treatment outcomes. Among them, the shape and position of the attachment [ 4 ] and the CAT material and thickness [ 5 , 6 ], are noted. Simultaneously, some are related to the patient’s physiology such as bone density [ 7 ], tooth crown and root shape [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although attachments have great potential, their use in dental practice is restricted because just a few studies have evaluated its mechanical behaviour, 10 - 12 and there is a significant gap of information about the biomechanical performance of these accessories based on their size, geometry, and forces. 9 , 10 Although the study of Dasy et al 11 observed higher retention force for beveled attachments than rectangular or ellipsoid ones, and Cai et al 10 optimized an attachment for tooth translation, no study evaluated the efficacy of attachments for tooth extrusion.…”
Section: Introductionmentioning
confidence: 99%